Cost-Effectiveness of Screening and Treatment for Cervical Cancer in Tanzania: Implications for other Sub-Saharan African Countries - Nelson, Stephanie (Value Health Reg Issues, 2016)
OBJECTIVES: To compare the institutional cost per person of screening and treatment between two groups of patients—those screened and those not screened before treatment for cervical cancer at Ocean Road Cancer Institute (ORCI) in Dar es Salaam, Tanzania—and to perform a cost-effectiveness analysis of the ORCI cervical cancer screening program. METHODS: The study included 721 screened and 333 unscreened patients treated at ORCI for cervical cancer from 2002 to 2011. We compared the cost of cervical cancer treatment per patient with life-years gained for patients screened at ORCI versus not screened. RESULTS: Patients with cancer were diagnosed at an earlier stage after participating in screening compared with nonparticipants. For example, 14.0% of stage I cancer patients had received screening by ORCI compared with 7.8% of unscreened cases. For stage IV cancer, these percentages were 1.4% and 6.9%, respectively. Average screening and treatment cost for patients receiving cancer screening ($2526) was higher than that for unscreened patients ($2482). However, we calculated an incremental cost-effectiveness ratio of $219 per life-year gained from receiving cervical cancer screening compared with not being screened, and thus the ORCI screening program was highly cost-effective. Furthermore, the screening program was associated with averting 1.3 deaths from cervical cancer each year resulting from earlier diagnoses of cancer cases, with the incremental cost-effectiveness ratio of $4597 per life saved. CONCLUSIONS: Although Sub-Saharan Africa faces substantial challenges in population health management, our study highlights the potential benefits from expanding access to regular cervical cancer screening for women in this region.